Analisa Kepuasan Pengunjung di Objek Wisata Pemandian Kaliwetan Menggunakan Algoritma Naïve Bayes - Zer, P. P.P.A.N.W.Fikrul Ilmi R.H.; Windarto, Agus Perdana (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
This research assesses visitor satisfaction with the Kaliwetan Bathing Place tourist destination located in Karang Anyer Village, Gunung Maligas District, Simalungun Regency. These services include swimming pools, lodges, prayer rooms, canteens, toilets, and parking lots along with the use of Kaliwetan Baths and its natural water management system. Visitors who came were quite a lot in the first years, and in its development the number of tourists experienced a significant decline. In the context of applying Naïve Bayes algorithm to classify visitor satisfaction, which is very important for the growth of tourist population, this study was made. The results obtained are as follows; the model accurately predicts that 94 visitors are satisfied and 26 visitors are dissatisfied, with a data mining efficiency of 96.67%. The classification results show that although the majority of visitors are satisfied, there are 20% of visitors who are dissatisfied and the complaints may be caused by unsatisfactory facilities and services. This research provides suggestions to the manager of Kaliwetan Bath on how to improve the overall service and infrastructure that will increase the attraction of tourists to the area. The Naïve Bayes model used can be a starting point that can be used by the manager to make decisions related to services related to cleanliness, safety, and visitor comfort.